NE UMABİLİRİM? KANT’IN AHLAK FELSEFESİNDE UMUT KAVRAMI - Tan, Necmettin (Fırat University, 2014)
Kanttan önce umut daha çok psikolojik ve dinsel bir kavram olarak ele alınırken Kant ile birlikte umut artık felsefi bir kavram olmuştur. Kant ilk defa umudu felsefi bir öğe olarak kullanmıştır. Felsefe geleneğinde umut olumsuz bir öğe olarak görülürken, dinsel gelenekte umut olumlu bir öğedir. Dinsel gelenekte umudun kaynağı Tanrı’dır. Kant’ta ise umut insanın sorduğu en önemli 3 sorudan birisidir. Kant’ın “Ne umabilirim” şeklinde formüle ettiği bu soru Kant’a göre diğer iki soru kadar, yani “ne bilebilirim ve ne yapmalıyım sorusu kadar kaçınılmaz ve önemlidir. Ona göre umut insan rasyonelliğinin zorunlu bir parçasıdır. Kant Tanrı’dan umuda gitmek yerine umuttan Tanrı’ya gitmeye çalışır. Sonuçta umut etmeyen bir kişinin Tanrı’dan söz etme gereği de yoktur

The concept of Hope, before Kant, was usually regarded as a psychological and religious issue. Kant used the concept of hope as a philosophical one, moreover he is the one who first employed the concept of hope as a philosophical element. Hope, in philosophical tradition, had been used as a negative element whereas religious tradition had used it as a positive one. In religious tradition, the source of hope is God. In Kant, though, hope is one of the most important three questions men ask. Kant formulated this question as “what may I hope?” This question, according to Kant is as inevitable and also important as other two question: What may I know? And what should I do? For him hope is essential to human rationality. Kant follows a path from hope to God rather than from God to hope. Consequently, he who does not hope needs not to think about God
What may I hope? The Concept of Hope in Kant’s Moral Philosophy